TELAAH NILAI PEPATAH MINANGKABAU SASEK DI UJUANG JALAN SURUIK KA PANGKA JALAN DAN KONTRIBUSINYA DALAM KONSELING BUDAYA - Zubaidah Zubaidah (Alfuad: Jurnal Sosial Keagamaan, 2019)
Minangkabau has a unique culture, that is always thriving one of them in social interaction using the proverb. Sasek di ujuang jalan suruik ka pangka jalan is a proverb full of values. This research aims to explore the values contained in the proverb Sasek di ujuang jalan suruik ka pangka jalan, and the contribution to cultural counseling. The research method used is qualitative hermeneutics. The results of the study is; (1) the value contained in the proverbial Sasek di ujuang jalan suruik ka pangka jalan is the need for exploration in finding the cause of the problem, (2) Every problem has a way out, and (3) cultural elaboration in counseling will facilitate the counseling process.